Gene expression, molecular docking, and molecular dynamics studies to identify potential antifungal compounds targeting virulence proteins/genes VelB and THR as possible drug targets against Curvularia lunata - Kamboj, Himanshu; Gupta, Lovely; Kumar, Pawan; Sen, Pooja; Sengupta, Abhishek; Vijayaraghavan, Pooja (Frontiers in Molecular Biosciences, 2022)
Curvuluria lunata is a melanized fungus pathogenic to both plants and animals including humans, causing from mild, febrile to life-threatening illness if not well treated. In humans, it is an etiological agent of keratomycosis, sinusitis, and onychomycosis in immunocompromised and immunocompetent patients. The development of multiple-drug-resistant strains poses a critical treatment issue as well as public health problem. Natural products are attractive prototypes for drug discovery due to their broad-spectrum efficacy and lower side effects. The present study explores possible targets of natural antifungal compounds (α-pinene, eugenol, berberine, and curcumin) against C. lunata via gene expression analysis, molecular docking interaction, and molecular dynamics (MD) studies. Curcumin, berberine, eugenol, and α-pinene exhibited in vitro antifungal activity at 78 μg/ml, 156 μg/ml, 156 μg/ml, and 1250 μg/ml, respectively. In addition, treatment by these compounds led to the complete inhibition of conidial germination and hindered the adherence when observed on onion epidermis. Several pathogenic factors of fungi are crucial for their survival inside the host including those involved in melanin biosynthesis, hyphal growth, sporulation, and mitogen-activated protein kinase (MAPK) signalling. Relative gene expression of velB, brn1, clm1, and pks18 responsible for conidiation, melanin, and cell wall integrity was down-regulated significantly. Results of molecular docking possessed good binding affinity of compounds and have confirmed their potential targets as THR and VelB proteins. The docked structures, having good binding affinity among all, were further refined, and rescored from their docked poses through 100-ns long MD simulations. The MDS study revealed that curcumin formed a stable and energetically stabilized complex with the target protein. Therefore, the study concludes that the antifungal compounds possess significant efficacy to inhibit C. lunata growth targeting virulence proteins/genes involved in spore formation and melanin biosynthesis.